2022
DOI: 10.3390/su142113816
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Emission Control Technology in Port Areas with Customers’ Low-Carbon Preference

Abstract: The choice of emission control technology in a port supply chain under a cap-and-trade scheme considering low-carbon preferences of customers, is explored in this study. In port areas, the port supply chain consisting of one port and one ship can adopt either shore power (SP) or low sulfur fuel oil (LSFO) to reduce emissions. The economic and social performance of the port supply chain when either SP or LSFO is implemented is compared under three different game models (port-leader Stackelberg game, ship-leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The study concluded that the most suitable methods are fully electric or diesel-electric hybrid solutions. Zhou and Zhang [6] considered the economic and social performance based on the fuel type of ships to study emission control technologies in the port supply chain within a cap-and-trade scheme. To reduce carbon emissions from ships, various efforts are being made to manage ship operations, analyze the performance of ship components, and consider alternative fuels.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The study concluded that the most suitable methods are fully electric or diesel-electric hybrid solutions. Zhou and Zhang [6] considered the economic and social performance based on the fuel type of ships to study emission control technologies in the port supply chain within a cap-and-trade scheme. To reduce carbon emissions from ships, various efforts are being made to manage ship operations, analyze the performance of ship components, and consider alternative fuels.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Consequently, China has implemented a series of measures at the national level, including the establishment of a carbon trading market, aimed at providing policy support to encourage emission reduction efforts. Research by ZHOU H and Ghosh [1,2] provides insights into selecting appropriate emission control technologies, especially through the comparison of the impacts of shore power (SP) and low sulfur fuel oil (LSFO). Facing the challenge of emission reduction, ports and shipping companies need to adopt green technologies, such as shore power and low sulfur fuel oil, to reduce carbon emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Governments are enacting relevant laws and regulations to reduce emissions in port operations, and some countries, such as the US, Canada, and China, have established Emission Control Areas (ECAs) in their coastal regions [10,11]. On the other hand, the development of green technologies, such as tail gas scrubbers, liquefied natural gas (LNG), and shore power technology, offers opportunities for port operations to reduce emissions [12][13][14]. However, the heavy investment and retrofitting costs associated with these technologies make it challenging for ports and shipping companies to implement such technologies [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have identified government subsidies and low-carbon preferences as key factors that can influence the decision of ports and shipping companies to invest in emission-reduction technologies [14,23,24]. However, some key questions regarding government subsidies and other related factors are still not well answered:…”
Section: Introductionmentioning
confidence: 99%